External validation of the HCM Risk-Kids model for predicting sudden cardiac death in childhood hypertrophic cardiomyopathy. (14th October 2021) - Norrish, G; Qu, C; Field, E; Cervi, E; Elliott, P; Ho, C; Omar, R; Kaski, J P; ,
Abstract: Background: Sudden cardiac death (SCD) is the most common mode of death in childhood hypertrophic cardiomyopathy (HCM). The newly developed HCM Risk-Kids model provides clinicians with individualised estimates of risk. The aim of this study was to externally validate the model in a large independent, multi-centre patient cohort. Methods: A retrospective, longitudinal cohort of patients diagnosed with HCM aged 1–16 years independent of the HCM-Risk-Kids development and internal validation cohort was studied. Data on HCM Risk-Kids predictor variables (unexplained syncope, non-sustained ventricular tachycardia, maximal left ventricular wall-thickness, left atrial diameter and left ventricular outflow tract gradient) were collected from the time of baseline clinical evaluation. The performance of the HCM Risk-Kids model in predicting risk at 5 years was assessed. Results: The cohort consisted of 421 patients with a median age at baseline evaluation of 12.3 years (IQR 7.3, 14.4). Over a median total follow up 3.48 years (IQR 1.83, 6.62, range 1 month – 20.7 years). Fourteen patients (3.3%) died and 10 (2.4%) underwent cardiac transplantation. Twenty-three patients (5.4%) met the SCD end-point within 5-years, with an overall incidence rate of 2.03 per 100 patient years (95% CI 1.48–2.78). Model validation showed a Harrell's C-index of 0.745 (95% CI 0.52–0.97) and Uno's C-index 0.714 (95% 0.58–0.85) with a calibration slope of 1.15 (95% 0.51–1.80). Figure 1a describes the agreement between predicted and observed 5-year cumulative proportion of SCD or equivalent events for each tertile of predicted risk in one imputed data set. One hundred and twenty-five (29.7%) patients had a predicted 5-year risk of ≥6%. SCD events occurred in 6 patients (2.0%) with a predicted risk <6% and 17 (13.6%) with a predicted risk ≥6. A 5-year predicted risk threshold of ≥6% identified 17 (73.9%) SCD-events with a corresponding C-statistic of 0.702 (95% CI 0.60–0.81) (Figure 1b). Conclusions: This study reports the first external validation of the HCM Risk-Kids model in a large and geographically diverse patient population. A 5-year predicted risk of ≥6% identified over 70% of events, confirming that HCM Risk-Kids provides a method for individualised risk predictions and shared decision making in children with HCM. Incorporation of the model into routine clinical care will enable independent prospective model validation and assessment of the effect of its use in clinical practice. FUNDunding Acknowledgement: Type of funding sources: Private grant(s) and/or Sponsorship. Main funding source(s): British Heart FoundationMedical Research Council